FORKED MOVING CONTACTS IN POWER CIRCUIT BREAKERS: SOLUTION TO CONSTANT POWER LOSSES INCURRED IN THE USE OF SERIES SHORT-CIRCUIT CURRENT LIMITING REACTORS ON FEEDERS (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
This paper develops a novel strategy for mitigating the limitations in the use of series short circuit Current Limiting Reactor (CLR) on feeders. The methodology involves the use of forked moving contacts for parallel operation of short circuit Current Limiting Reactor and current conducting bars similar to, but better than both the parallel operation of IS- Limiter and Current limiting reactor and the Improved IS- Limiter Technique for implementing fault current limiting reactors on feeders at no constant power losses [1,2].